Towards systematic software reuse of GIS: Insights from a case study - Buccella, Agustina (2013)
With the development and adoption of geographic information systems, there is an increasingly amount of software resources being stored or recorded as products to be reused. At the same time,complexity of geographic services is addressed through standardization, which allows developers reaching higher quality levels. In this paper, we introduce our domain-oriented approach to developing geographic software product lines focusing on the experiences collected rom a case study. It was developed in the Marine Ecology Domain (Patagonia, Argentina) and illustrates insights of the process.